The Current State of Digital Policy In The Republic Of Kazakhstan - Amirbek А.; Ongarova Е.; Syzdykova Г. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The article examines the problem of the prospective application of the concept of digitalization in various spheres of social development, primarily in the political sphere from the point of view of the formation of the digital economy. The use of digital technologies in politics is viewed through the prism of two discourses: the digitization of politics is the policy of digitization associated with the expansion of technology into political relations and political management of digital development in the economy and social sphere. The first discourse highlights the mechanisms for determining political interests through electronic appeals to social networks and online voting. Within the framework of the discourse of digitalization policy, the creation of a management system for the development of the digital economy in the Republic of Kazakhstan is considered in connection with the implementation of one of the national goals of the country for the period 2018-2022. regulatory activities of the state as a whole to ensure the rapid introduction of digital technologies in the economy and social sphere, as well as the formation of the foundations of appropriate policy, namely, efforts to form and create their own national model of managing processes in the digital space. Both discourses demonstrate a tendency to a deep synthesis of the processes of technological and social development, which makes the latter connected by roots that lose their dependence on the mediating functions of traditional institutions. The growing importance of digital formats in world politics forces the state to mobilize various available tools to reduce the risks of competition in the new space of social relatio